2006
DOI: 10.1104/pp.105.075671
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Modulates Flavonoid Accumulation and Gravitropic Responses in Roots of Arabidopsis

Abstract: Plant organs change their growth direction in response to reorientation relative to the gravity vector. We explored the role of ethylene in Arabidopsis (Arabidopsis thaliana) root gravitropism. Treatment of wild-type Columbia seedlings with the ethylene precursor 1-aminocyclopropane carboxylic acid (ACC) reduced root elongation and gravitropic curvature. The ethyleneinsensitive mutants ein2-5 and etr1-3 had wild-type root gravity responses, but lacked the growth and gravity inhibition by ACC found in the wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
139
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 73 publications
(134 reference statements)
8
139
0
Order By: Relevance
“…Basipetal auxin transport may also be regulated by molecules affecting the activity, expression and subcellular localization of auxin transporters in the lateral cell files of the root (as reviewed by Muday and Rahman, 2007). In addition to auxin, other hormones or signaling molecules such as cytokinins (Aloni et al, 2004), reactive oxygen species (Joo et al, 2001), flavonoids and ethylene (Buer and Muday, 2004;Buer et al, 2006) may be involved in the growth response phase of gravitropism through control of differential elongation, either in parallel with auxin or as regulators of the auxin-mediated signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Basipetal auxin transport may also be regulated by molecules affecting the activity, expression and subcellular localization of auxin transporters in the lateral cell files of the root (as reviewed by Muday and Rahman, 2007). In addition to auxin, other hormones or signaling molecules such as cytokinins (Aloni et al, 2004), reactive oxygen species (Joo et al, 2001), flavonoids and ethylene (Buer and Muday, 2004;Buer et al, 2006) may be involved in the growth response phase of gravitropism through control of differential elongation, either in parallel with auxin or as regulators of the auxin-mediated signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…genetic evidence suggests that a variety of root developmental processes, including elongation, gravitropism, and lateral root formation, are regulated by cross talk between these two hormones (Rahman et al, 2001;Buer et al, 2006;Rů zicka et al, 2007;Stepanova et al, 2007;Swarup et al, 2007;Negi et al, 2008Negi et al, , 2010. The ethylene-and auxin-signaling pathways have been extensively studied, and studies employing global gene expression analyses and the unique genetic tools available in Arabidopsis (Arabidopsis thaliana) have identified a number of the key signaling proteins as well as the transcriptional response targets (Kendrick and Chang, 2008;Chapman and Estelle, 2009).…”
mentioning
confidence: 99%
“…Genes encoding enzymes of flavonoid metabolism may be among these ultimate targets of auxin and ethylene transcriptional networks. Previous studies have suggested that flavonol accumulation may be induced by both auxin and ethylene and have implicated these specialized metabolites in hormone-dependent developmental pathways (Buer and Muday, 2004;Buer et al, 2006) but have not examined whether this accumulation is transcriptionally regulated.…”
mentioning
confidence: 99%
“…In addition to oxylipins, ethylene has also been implicated in the activation of systemic plant defenses in response to pathogens (Penninckx et al, 1998) and wounding (O'Donnell et al, 1996). In Arabidopsis, ethylene also provokes an increase in flavonoid accumulation (Buer et al, 2006) and in carrot (Daucus carota) induces genes for flavonoid synthesis (Ecker and Davis, 1987). The JA and ethylene signaling pathways are induced concomitantly in Arabidopsis to activate defense responses after infection with a necrotrophic pathogen (Penninckx et al, 1998), but, after wounding, an antagonistic interaction between JA and ethylene was proposed for the local responses in Arabidopsis leaves (Rojo et al, 1999).…”
mentioning
confidence: 99%